Resveratrol and Quercetin: Novel Polyphenolic Chemopreventive Agents - Mohammad Younis Bhat; Samina Farhat; Sheikh Shoib; Zorawar Singh (International Journal of Phytomedicine, 2014)
Cancer continues to be a major public health concern worldwide and the main modalities for treatment include chemo and/or radiotherapy and surgery which are often commonly used in conjuction to control and treat cancer. Recent advances in the area of cancer prevention have opened new avenues for research and several medicinal plants are being used to prevent and cure a variety of diseases, including oncological ailments. Herbal drugs have been in use for several thousands of years in various traditional systems of medicine existing in different parts of the world. In recent years, there has been a paradigm shift in the way we look at herbals which today are being viewed as potential agents for tackling various diseases, particularly for which there is no effective cure available in modern system of medicine or when the side effects of synthetic drugs are too many. It has been estimated by the World Health Organization (WHO) that currently 80% of the world’s population is still dependent on herbal drugs for solving their health needs in one or the other way. They are less toxic alternatives to modern medicine, offer much scope for prevention of diseases, are easily available, cheaper costs, effective nature and promise to cure the so far incurable diseases like cancer, AIDS, hepatitis C, Alzheimer’s and Parkinson’s disease, diabetes makes them much sought for. Chemoprevention offers a promising approach to primary cancer prevention for a variety of organs. A plethora of compounds, including several promising plant derived compounds are being evaluated in the laboratories and two phytocompounds which hold a lot of promise include resveratrol and quercetin – as novel chemopreventive agents.